(untitled) (Fiep Bulletin - online, 2012)
Acromegaly is a debilitating and disfiguring disease due to excessive growth hormone (GH) and insulin-like 1 growth factor (IGF-1), with the result in hypersomatotropic manifestations, and specific effects of the tumor mass itself, interfering directly with the quality of Life (QOL) of patients. It is considered a rare disease and due to the insidious character and the lack of knowledge in the general population, as well as within health professionals, making the diagnosis usually occurs at a later life stage, between the fourth and fifth decades of life. This study aimed to determine the prognosis of acromegaly diagnosed and treated in the city of Bandeirantes, analyzing the time of diagnosis, disease progression and QOL of these people. The study was developed with cross sectional, observational and descriptive approach and conducted from January to July 2011. To ensure the privacy of patients, they were named Orquídea and Margarida. To ascertain the quality of life of acromegalic patients, they have received a questionnaire specific for this disease called AcroQoL. According to the AcroQoL Orquídea got a score of 62.5%, while Margarida reached 53.4%, so it was observed that the patient Orquídea boasts a better QOL. The evolution of the cases relevant to the study occurred in a different way which is that a patient who was diagnosed later showed worse disease progression and consequent worse QOL. Therefore, knowledge about the disease within health professionals it is essential for early diagnosis and consequently better QOL for these patients.